A before and after study assessing the impact of a new model for recognizing and responding to early signs of deterioration in an acute hospital. (28th March 2012) - McDonnell, Ann; Tod, Angela; Bray, Kate; Bainbridge, Derek; Adsetts, Dawn; Walters, Stephen
Abstract Aim. To evaluate the impact of a new model for the detection and management of deteriorating patients on knowledge and confidence of nursing staff in an acute hospital. Background. International evidence shows that clinical deterioration is not always recognized or acted on by nurses. The use of physiological track and trigger scoring systems accompanied by a graded response strategy has been recommended to monitor all adult patients in acute UK hospitals. However, little is known about the impact of these new systems in practice. Design. A single centre, mixed methods before‐and‐after study. Methods. A mixed methods before‐and‐after study, set in a district general hospital in England, in 2009, including a survey (n = 213) and qualitative interviews (n = 15) with nursing staff. The questionnaire examined knowledge and confidence in recognition and management of deteriorating patients 6 weeks before and after an intervention which included training, new observation charts and a new track and trigger system. Interviews further explored participants' perspectives. Comparisons were made between registered and unregistered nurses. Results. Following the intervention, knowledge, and confidence to recognize and manage deteriorating patients increased; the number of concerns were reduced. Scores were higher for registered than unregistered nurses before and after the intervention. Interviews confirmed these findings and provided detail on how nurses felt the new system had improved practice. Conclusion. The new model had a positive impact on the self‐assessed knowledge and confidence of registered and unregistered nurses. Similar initiatives should take into account the clinical context and tailor training packages accordingly.